If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16z + -5z = 0 Combine like terms: 16z + -5z = 11z 11z = 0 Solving 11z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '11'. z = 0 Simplifying z = 0
| 4x-7+6x=53 | | 2x+5x+4= | | (p)(p)-4=5p-10 | | 2(172x+107)= | | 10-x-6x=-32 | | 2x+9+3x=-1 | | v-2.4=-4.7 | | m-3=125 | | (2x+14)=90 | | (3x+21)=90 | | (4x+60)=180 | | 81/6/n=51/2/71/3 | | (12+l)+l=72 | | 18-2q=4q | | 4*7.5+60= | | 12l+l=72 | | 3(2x-6)+5=2x-3 | | 4*7.5+60=90 | | 2y+27=57 | | 4x+60=90 | | 1/4x=950 | | 0.2x+24.8=36 | | 9-(3n-1)=7-4n | | 3(m+9)=60 | | 7v=2w-20 | | 9-2x=27 | | 9-2x=27 | | 2(3x+5)=-50+6 | | 4y=8x-x^2 | | 3n+78=81 | | x-x^3=404 | | 5ln(4x-3)=15 |